2014
DOI: 10.1098/rsta.2013.0190
|View full text |Cite
|
Sign up to set email alerts
|

Survival of fossils under extreme shocks induced by hypervelocity impacts

Abstract: Experimental data are shown for survival of fossilized diatoms undergoing shocks in the GPa range. The results were obtained from hypervelocity impact experiments which fired fossilized diatoms frozen in ice into water targets. After the shots, the material recovered from the target water was inspected for diatom fossils. Nine shots were carried out, at speeds from 0.388 to 5.34 km s−1, corresponding to mean peak pressures of 0.2–19 GPa. In all cases, fragmented fossilized diatoms were recovered, but both the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…For example, it is estimated that on average there is *1-2 ppm of terrestrial material at the lunar surface today, however, some areas of the surface may have higher concentrations (Armstrong 2011). As impact collision speeds from terrestrial material are relatively low (peaking at *3 km/s; Armstrong 2011), it has been demonstrated that terrestrial material may well survive peak shock pressures remaining intact after impact (Crawford et al 2008;Burchell et al 2014b). Such considerations imply the possibility that the lunar surface preserves material delivered from the Hadean or early Archean Earth, preserving key chemical and isotopic information about the early history of our planet and potentially even preserving remnants of fossil life (Burchell et al 2014b) and early biological processes (Matthewman et al 2015).…”
Section: Materials Derived From the Earth And Other Planetsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, it is estimated that on average there is *1-2 ppm of terrestrial material at the lunar surface today, however, some areas of the surface may have higher concentrations (Armstrong 2011). As impact collision speeds from terrestrial material are relatively low (peaking at *3 km/s; Armstrong 2011), it has been demonstrated that terrestrial material may well survive peak shock pressures remaining intact after impact (Crawford et al 2008;Burchell et al 2014b). Such considerations imply the possibility that the lunar surface preserves material delivered from the Hadean or early Archean Earth, preserving key chemical and isotopic information about the early history of our planet and potentially even preserving remnants of fossil life (Burchell et al 2014b) and early biological processes (Matthewman et al 2015).…”
Section: Materials Derived From the Earth And Other Planetsmentioning
confidence: 99%
“…As impact collision speeds from terrestrial material are relatively low (peaking at *3 km/s; Armstrong 2011), it has been demonstrated that terrestrial material may well survive peak shock pressures remaining intact after impact (Crawford et al 2008;Burchell et al 2014b). Such considerations imply the possibility that the lunar surface preserves material delivered from the Hadean or early Archean Earth, preserving key chemical and isotopic information about the early history of our planet and potentially even preserving remnants of fossil life (Burchell et al 2014b) and early biological processes (Matthewman et al 2015). Remnants of such early Earth geological materials might challenging to identify in regolith materials, but could be identified from the presence of mineral or rock debris from komatiite lavas (that were dominant in the early Earth's crust), hydrated or oxidised minerals, sedimentary rocks (e.g.…”
Section: Materials Derived From the Earth And Other Planetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ejected fragments of planetary surfaces could potentially have contained organic matter, including biological material. The potential for preservation of the earliest biotic and prebiotic material in terrestrial or martian meteorites is a key motivation for exploration of the Moon (Crawford et al, 2008;Burchell et al, 2014b). Recent experimental work has shown the ability of organic biomarkers to survive the impact shock conditions that would have ejected this material from the planetary surface (e.g., Parnell et al, 2010;Burchell et al, 2014a).…”
Section: Sources Of Organic Matter To the Moonmentioning
confidence: 99%
“…The Moon may provide us with this archive (Armstrong et al, 2002;Crawford et al, 2008;Joy et al, 2012;Burchell et al, 2014b). Major surface volcanic activity on the Moon ceased around 3.1 Ga (Wilhelms et al, 1987).…”
Section: Organic Records In the Solar Systemmentioning
confidence: 99%